War narratives, survivalism and trauma in Uzodinma Iweala's beast of no nation and Ishmael Beah's a long hay gone (2022)
In recent history, African writers and literary scholars have become pre-occupied with the discourse of war, violence and trauma in their creative and critical engagements. The themes of violent deaths, social angst and widespread disillusionment that presently characterize African society remain at the front burner of contemporary African discourse. This study, therefore, examines the socio-historical contexts of war narrative, survivalism and trauma in Uzodinma Iweala's Beast of No Nation and Ishmael Beah's A Long Way Gone Several critics have largely focused on thematic preoccupations such as death, violence, child soldiering, loss of identity, slaughter of innocence and even trauma, but little attention has been paid to the motif of survivalism and trauma in these war narratives, complemented by the exploration of post-traumatic stress techniques. Cathy Caruth's concept of trauma, complemented by Judith Herman's notion of trauma and recovery\ serves as theoretical framework of this paper Using the qualitative research as methodology, the paper critically explores the motif of survivalism vis-a-vis the experiences of victims of war and the postwar realities that these narratives tell, with the view to redefining human perception of war and its aftermaths